2014
DOI: 10.1016/j.eururo.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Analytic and Clinical Validation of a Prostate Cancer–Enhanced Messenger RNA Detection Assay in Whole Blood as a Prognostic Biomarker for Survival

Abstract: Background Biomarkers based on detecting prostate cancer-specific transcripts are associated with inferior outcomes, but their validation in a clinical context is lacking. Objective To determine whether detecting prostate cancer enhanced transcripts in whole blood using an analytically valid assay has prognostic significance relative to circulating tumor cell (CTC) enumeration. Design, Setting, and Participants The predictive value for overall survival of the detection in whole blood by reverse transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 26 publications
0
74
0
Order By: Relevance
“…Similar methodologies are evolving for solid tumors, e.g. MACC1 in gastric cancers (Burock et al 2015) or a panel of prostate cancer-associated genes in prostate cancer (Danila et al 2014). Hematological cancer measurements clearly reflect a pathobiological process as expression of fusion transcript levels correlate well (R 2 Zw0.5) between bone marrow and blood (Ostergaard et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Similar methodologies are evolving for solid tumors, e.g. MACC1 in gastric cancers (Burock et al 2015) or a panel of prostate cancer-associated genes in prostate cancer (Danila et al 2014). Hematological cancer measurements clearly reflect a pathobiological process as expression of fusion transcript levels correlate well (R 2 Zw0.5) between bone marrow and blood (Ostergaard et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recently Danila et al investigated the detection of CTCs and the expression of five genes frequently detected in PCa cells (but not in peripheral mononuclear cells) utilizing reverse transcriptase-polymerase chain reaction (RT-PCR) to detect transcripts from peripheral blood [92]. Both unfavorable CTC count (five or more cells) and detection of two or more gene transcripts had similar significant prognostic value for risk of PCa death, and when combined, additional prognostic value was demonstrated.…”
Section: 5mentioning
confidence: 99%
“…As such, other liquid biopsy techniques including circulating cell-free tumor DNA may help to identify genomic alterations and track patient's genomic landscape over time to assess individual prognosis and adapt further treatment strategies. [37,38] The RT-PCR [45]. After combining the results of gene profile with CTCs counts, risk group were defined to pinpoint patients with poor prognosis.…”
Section: Prognostic Biomarkers In Crpcmentioning
confidence: 99%
“…After combining the results of gene profile with CTCs counts, risk group were defined to pinpoint patients with poor prognosis. This RT-PCR assay detecting prostatespecific RNA in whole blood associated with CTCs count is currently being prospectively tested as a prognostic factor and response indicator [45]. Loss of PTEN expression has also been reported to be associated with worse survival [46] and analyses of extracellular microRNAs embedded in circulating exomes revealed that plasma exomal miR-1290 and miR-375 could be promising prognostic biomarkers for CRPC patients [47].…”
Section: Prognostic Biomarkers In Crpcmentioning
confidence: 99%